2010
DOI: 10.1080/02626660903529023
|View full text |Cite
|
Sign up to set email alerts
|

Producing time series of river water height by means of satellite radar altimetry—a comparative study

Abstract: Satellite radar altimetry is complementary to in situ limnimetric surveys as a means of estimating the water height of large rivers, lakes and flood plains. Production of water height time series by satellite radar altimetry technology requires first the selection of radar ground target locations corresponding to water body surfaces under study, i.e. the definition of "virtual limnimetric stations". We propose to investigate qualitative and quantitative differences between three representative virtual station … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
22
0

Year Published

2010
2010
2017
2017

Publication Types

Select...
8
1

Relationship

4
5

Authors

Journals

citations
Cited by 31 publications
(24 citation statements)
references
References 22 publications
0
22
0
Order By: Relevance
“…Many studies have now shown the great ability of radar altimetry missions for retrieving river stages [53][54][55][56][57]. In this study, we used data from three different radar altimeters, namely ENVISAT/RA-2, T/P and ICESat/GLAS, available through the CTOH website (Centre de Topographie des Océans et de l'Hydrosphère) [58].…”
Section: Radar Altimetry Datamentioning
confidence: 99%
See 1 more Smart Citation
“…Many studies have now shown the great ability of radar altimetry missions for retrieving river stages [53][54][55][56][57]. In this study, we used data from three different radar altimeters, namely ENVISAT/RA-2, T/P and ICESat/GLAS, available through the CTOH website (Centre de Topographie des Océans et de l'Hydrosphère) [58].…”
Section: Radar Altimetry Datamentioning
confidence: 99%
“…Satellite radar altimetry provided 5 additional virtual stations from the T/P and ENVISAT missions. The manual method described in [53,59] was used to build the virtual gauges, which can be defined as any intersection between a water body surface and radar altimetric ground tracks. Three virtual stations were gained from the ENVISAT mission ( Figure 1): SV2 (3.493˝S, 60.253˝W) in the upstream zone, SV1 (3.392˝S, 60.239˝W) in the downstream zone and SVR (3.325˝S, 60.220˝W) in the Solimões.…”
Section: In Situ Datamentioning
confidence: 99%
“…In all other situations, manual extraction has been performed, with results slightly better (lower standard deviation and more cycles sampled) than the automatic one. The automatic extraction has been found to be more reproductible, and not statistically different than the manual one 16 . The reproductibility criteria is certainly best fulfilled by the automatic method, but it seems that in the cases where the river is mostly perpendicular to the flow direction, with small width, and extensive floodplain, the manual extraction can be the best method to employ.…”
Section: Comparison Of Methodsmentioning
confidence: 98%
“…Hence, many methodologies have been developed for selection of waveform over the inland water bodies, i.e. defining the virtual station (Berry et al, 2005;Leon, 2006;Kouraev et al, 2004;Zakharova et al, 2006;Roux et al, 2010). In many of the research studies over large rivers, virtual stations are defined using the satellite information of river flow characteristics.…”
Section: Introductionmentioning
confidence: 99%